The Influence of Product Quality and Price on The Purchase Decision of Heyjo Bakpao in Singgahan, Tuban (A Case Study of Local Micro, Small, and Medium Enterprises) - Awaludin Ridwan; Ahmad Fanani (International Journal of Economics, Business and Innovation Research, 2025)
The current economic development of society is growing rapidly, evidenced by the emergence of numerous business actors aiming to produce goods and services, thereby making the community more active in determining and deciding their needs. Business actors are competing to implement various marketing strategies to capitalize on market opportunities by offering products that align with consumers' desires and needs. Bakpao is a type of food that is widely enjoyed by the Indonesian people. Bakpao Heyjo is one of the producers and sellers of bakpao, established in 2022 in Kedungjambe Village, Singgahan Sub-district, Tuban Regency, offering a variety of flavors at affordable prices. Bakpao Heyjo has become a popular processed food choice that is easily accessible and offers a wide range of options. This study aims to analyze the influence of product quality and price on the purchase decision of bakpao. Heyjo consumers. Data was collected through a questionnaire distributed to consumers using a non-probability incidental sampling method. Responses were measured using a Likert scale. Data analysis was conducted using classical assumption tests and multiple linear regression through SPSS 20.0. The results of the study indicate that product quality and price simultaneously have a significant influence on purchasing decisions, contributing 79.8%. The remaining 20.2% is attributed to other variables not examined in this study. These findings suggest that improving product quality and maintaining competitive prices are key strategies for enhancing consumer purchasing decisions.